2008
DOI: 10.1177/0269881108092124
|View full text |Cite
|
Sign up to set email alerts
|

Depot and oral antipsychotics: patient preferences and attitudes are not the same thing

Abstract: Some clinicians believe that antipsychotic depot injections are unacceptable to patients. This cross-sectional study investigated patients' attitudes regarding antipsychotics, and included within-participant comparisons. Two hundred and twenty-two out-patients with schizophrenia/schizoaffective disorder completed the Drug Attitude Inventory (DAI-10), scales on insight, side effects and treatment preferences. Formulation preference was associated with current medication formulation: depots were preferred by 43%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 28 publications
5
67
1
1
Order By: Relevance
“…Other studies have showed that the correlations between side effects and drug attitude tend to be weak [24,33]. This study showed that drug attitude was not affected significantly by side effects.…”
Section: Discussionsupporting
confidence: 52%
“…Other studies have showed that the correlations between side effects and drug attitude tend to be weak [24,33]. This study showed that drug attitude was not affected significantly by side effects.…”
Section: Discussionsupporting
confidence: 52%
“…Similar findings were reported in a study of outpatients with schizophrenia or schizoaffective disorder in the United Kingdom. 124 Perceptions about LAI use may also differ among health care providers. In a survey in the United Kingdom, 125 most psychiatrists (91%) felt that LAIs were as efficacious as oral medications and improve patient adherence (81%) and prevent relapse (94%); however, despite this, 48% felt that depot medications are stigmatizing, and 69% believed LAI antipsychotics are less acceptable to patients.…”
Section: When To Consider Lai Treatment: Patient Eligibility and Selementioning
confidence: 99%
“…Patients or families may view the physician's recommendation of LAI therapy as a form of punishment or as a sign that the patient is very ill or has recently worsened. 124 However, it should be recognized that there are many different types of nonadherence. Some patients exhibit what might be referred to as "distracted nonadherence," which results from issues such as cognitive impairment or disorganization.…”
Section: 141mentioning
confidence: 99%
“…In cases where LAIs are offered, patient tend to show a more favourable attitude of LAIs which correlate with their knowledge of these formulations (Potkin et al 2013). This is supported by systematic review of 12 studies by Waddell and Taylor (2009) and several other studies (Heres et al 2007, Patel et al 2009, Waddell and Taylor 2009, Caroli et al 2011, Das et al 2014). …”
Section: Patient's Views Of Laismentioning
confidence: 82%